Efektivitas Bimbingan Perkawinan Pranikah Terhadap Terciptanya Keharmonisan Rumah Tangga - Andrika Riyansyah.L, M; Najwan, Johni; Alissa, Evalina (Zaaken: Journal of Civil and Business Law, 2023)
This study aims to find out and analyze how the implementation of premarital marriage guidance at the Office of Religious Affairs, Kota Baru District and what are the obstacles that occur in the implementation of premarital marriage guidance at the Office of Religious Affairs, Kota Baru District. The method used in this study is an empirical juridical research method, namely a legal research method that looks at the law in the true sense and how the law is in the community. In this study, the effectiveness of legal norms in this case is the Director General's Decree Number 379 of 2018 concerning Guidelines for the Implementation of Premarital Marriage Guidance for Bride and Groom Candidates. The result of this research is that premarital marriage guidance in Kota Baru District has been implemented. The marriage counseling was held at the Ministry of Religion and the Office of Religious Affairs in Kota Baru District. In the implementation of premarital marriage guidance, there are still many obstacles. Constraints experienced such as the lack of facilitators or resource persons who provide material, the lack of facilities and facilities due to the lack of budget in the implementation of the premarital marriage guidance. So that in the implementation of this guidance, there are differences in the guidance of premarital marriage that is conveyed to the prospective husband and wife. Abstrak Penelitian ini bertujuan untuk mengetahui dan menganalisis bagaimanakah pelaksanaan bimbingan perkawinan pranikah di Kantor Urusan Agama Kecamatan Kota Baru dan apa yang menjadi kendala yang terjadi dalam pelaksanaan bimbingan perkawinan pranikah di Kantor Urusan Agama Kecamatan Kota Baru. Metode yang digunakan dalam penelitian ini adalah metode penelitian yuridis empiris yaitu metode penelitian hukum yang melihat hukum dalam artian sebenar-benarnya serta bagaimana hukum dilingkungan masyarakat. Dalam penelitian ini melihat efektivitas norma hukum dalam hal ini adalah Keputusan Direktur Jenderal Nomor 379 Tahun 2018 Tentang Petunjuk Pelaksanaan Bimbingan Perkawinan Pranikah Bagi Calon Pengantin. Hasil dari penelitian iniÂ  bahwa bimbingan perkawinan pranikah di Kecamatan Kota Baru telah terlaksana. Bimbingan perkawinan tersebut diselenggarakan di Kementerian Agama dan Kantor Urusan Agama Kecamatan Kota Baru. Dalam penyelenggaraan bimbingan perkawinan pranikah tersebut masih banyak terjadi kendala-kendala. Kendala yang dialami seperti masih minimnya fasilitator atau narasumber yang memberikan materi, masih kurangnya sarana dan fasilitas yang disebabkan minimnya anggaran dalam penyelenggaraan bimbingan perkawinan pranikah tersebut. Sehingga dalam pelaksanaan bimbingan tersebut terdapat perbedaan bimbingan perkawinan pranikah yang disampaikan kepada pasangan calon suami istri. Â